First Trimester Screening by Ultrasonographic Markers For Prediction of Preeclampsia - Dr. Seema Pandey; Dr. Divya Gupta; Dr. Rakesh Kumar Shukla (International Journal of Medical Research and Review, 2022)
Aim- To correlate association of ultrasonographic markers in antenatal patients with subsequent development of preeclampsia Material Method - 131 pregnant women, in first trimester of pregnancy were investigated for their uterine artery Doppler and  placental volume. These patients were followed up till term for the development of preeclampsia. Results: Out of 131 antenatal cases 20.61% developed preeclampsia. Uterine artery Pulsatility index >95th percentile(>2.3) with mean 2.08±0.43(p value 0.0001) predicted pre eclampsia with sensitivity of 51.85% with specificity of 95.19%. Similarly Resistance index of Uterine artery >95th  percentile(>0.8) with mean 0.771±0.084(p value 0.018) predicted pre eclampsia with sensitivity of 48.15% and specificity of 87.50% . Placental Quotient <10th percentile (<0.81) with mean 0.89 (p value 0.0001)predicted pre eclampsia with sensitivity of 40.74% and specificity of 96%.On combining all three ultrasonographic parameters the sensitivity for prediction of preeclampsia was increased to 70.37% with specificity of 86.54%  with PPV of 36.74% % and NPV of 96.34% %.Conclusion: Maternal ultrasonographic markers like Uterine artery PI, RI, Placental Quotient levels vary between normal pregnancies and those that subsequently developed preeclampsia. Thus our study concludes that  first trimester screening with ultrasonographic markershave high sensitivity, specificity and negative predictive value in detection of preeclampsia.